Introducing principles of environmental comfort and control to support energy conservation in education buildings: project-based learning approach - Keshavarz, Mahboobeh (Kansas State University, 2021)
The construction of green schools in the U.S. has considerably soared in recent years. Sustainably designed schools come from not only energy savings, but also from wide-ranging, measurable student health and performance benefits associated with natural light and improved environmental quality. The flip side of sustainable buildings, however, is that technology and controls introduce a new level of complexity compared to conventional buildings. Building owners and occupants find it very difficult to navigate these controls. This results in an increase in energy expenditure of the buildings, while users fail to appreciate their environmental comfort. Therefore, education on environmental comfort in spaces and identifying building controls seems of great significance. By the same token, decisions made with regard to the operation of the controls by building users need special attention as it is directly related to energy saving. This study investigates the effect of Project-based Learning on increasing the knowledge level and changing attitudes and actions of green building occupants to conserve energy. Project-based Learning is an educational method where individuals are required to learn and apply the concepts through experience. Using this method enables building users to find answers to the real-world problems by testing their ideas while working in groups. This learning approach has also the capability to translate into changes in building users’ attitudes and actions related to energy conservation. To study the effect of this learning approach, data was collected from a total of 119 students from APD design community (Seaton and Regnier—newly constructed green school) at Kansas State University. A pre-knowledge survey was conducted initially to capture the general knowledge of the participants about comfort and controls. For the experiment, a series of class lectures and activities were devised to which students, based on the group they were categorized in, were exposed. The students for this study were grouped under three categories: 1) Traditional Learning group (control group) in which students required to only watch class lectures, 2) Individual Project-based Learning group in which students had to complete a series of individual class activities in addition to the tasks assigned to the control group, and 3) Peer Project-based Learning group in which students were asked to do peer-to-peer interaction for the class activities in addition to the tasks assigned to the other groups. After the experiment concluded, a follow-up survey was conducted to evaluate the impact of the activities on the improvements in knowledge and controls’ operation level of participants based on students’ self-report. By analyzing the results from the experiment, this study identifies that the groups that have received Project-based Learning module, generally, have used building lighting and dimming controls more than the control group. Particularly, the Peer PBL group was identified to be the group with significant change in knowledge level in this study. Class activities and peer interaction have highly affected students’ perspective towards energy savings and environmental satisfaction. Findings from the experiment confirmed that peers were recognized to be extremely influential in raising participants’ awareness and motivation towards operation of the controls, energy conservation, and environmental comfort.
Keywords: Green building controls; Environmental comfort; Energy conservation; Building occupants' education; Project-based learning module